Racial and Ethnic Disparities in Health Status, Chronic Conditions, and Behavioral Risk Factors Among Prostate Cancer Survivors, United States, 2015 - Atere-Roberts, Joëlle (Prev Chronic Dis, 2021)
INTRODUCTION: Little is known about perceived health status and behavioral risk factors among prostate cancer survivors. The objective of this study was to describe racial and ethnic differences in self-reported health status, chronic conditions, and selected behavioral risk factors among prostate cancer survivors in the US. METHODS: We used data from the 2015 National Health Interview Survey to calculate the prevalence of various levels of health status, chronic conditions, behavioral risk factors, and sociodemographic characteristics among prostate cancer survivors aged 50 years or older. We stratified results by race and ethnicity. RESULTS: Of the 317 prostate cancer survivors in our sample, 33.1% reported no physical activity, 64.2% reported being current drinkers, 26.1% characterized their drinking as moderate/heavy, 42.3% reported being former smokers, and 8.7% were current smokers. Nearly one-third (29.1%) of survivors were obese (body mass index ≥30), and 15.1% had 3 to 6 chronic conditions. A greater percentage of White (29.7%) than Black (14.2%) or Hispanic (16.3%) survivors were moderate/heavy drinkers. A greater percentage of Black (16.2%) than White (7.5%) or Hispanic (7.3%) survivors were current smokers. A greater percentage of Black (25.1%) or Hispanic (27.7%) than White (11.4%) survivors had 3 to 6 chronic conditions. CONCLUSION: As the population of older men increases, prostate cancer diagnoses and those surviving the disease will also increase. Significant racial and ethnic group differences in behavioral risk factors and chronic conditions exist among prostate cancer survivors. Public health could prioritize efforts to improve health behaviors among prostate cancer survivors and use targeted interventions to address disparities.